The influence of service flow changes and drug consultation on quality of life of HIV/AIDS-positive patients in Sunan Kalijaga regional public hospital, Demak regency - Dewi, Rissa Maharani; Akrom, Akrom; Simbara, Ari (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Human immunodeficiency virus (HIV infection/AIDS) cannot be cured but can be controlled by antiretroviral medicines. Non-compliance with the treatment is influenced by internal and external factors. The internal factors (predisposing factors) include healthcare systems, socioeconomic conditions, and patients. Meanwhile, the external factors (enabling and reinforcing factors) include the condition of the disease and therapy. This study aims to determine the influence of service flow changes and drug consultation on the quality of life of people living with HIV/AIDS in Sunan Kalijaga Regional Public Hospital, Demak Regency.This research employed a quasi-experimental method with one group and a pre-post design. The research subject was HIV/AIDS-positive patients in Sunan Kalijaga Regional Public Hospital, Demak Regency. These subjects had met the inclusion and exclusion research criteria. The data were collected using an in-depth interview, consisting of 14 questions to determine factors in non-compliance with treatment and patients' quality of life. Patient compliance with treatment and quality of life were measured before and after the intervention. The dependent t-test was employed to determine differences in the average score of the compliance and quality of life before and after the treatment. The majority of HIV/AIDS-positive patients in Sunan Kalijaga Regional Public Hospital are in the productive age (49 people or 96.22%), female (33 people or 62.24%), employed in private jobs (16 people or 30.19%), married (34 people or 64.2%), and graduated from primary school (20 people or 37.7%). The majority of the patients have undergone the treatment for > 1 year (32 respondents or 60.4%) and received the drug regimen of ZDV + 3TC + NVP (90.57%). There is no significant difference in the patient compliance with the treatment before and after the intervention with the sig < 0.05. Moreover, the patients have a high quality of life with a compliance value of 80-100% before and after the intervention. The pre-post-interventions have influenced the physical health domain and the social relation domain with the sig < 0.05. The provision of education affects the quality of life on physical health and social relationship factors (sig < 0.005). The implementation of drug consultation could improve the HIV-positive patients' quality of life in physical health and social relationship domains. In contrast, the intervention does not affect the patients' compliance with the therapy.